PENATALAKSANAAN HOLISTIK PADA ANAK PEREMPUAN 6 TAHUN DENGAN VARISELA MELALUI PENDEKATAN KEDOKTERAN KELUARGA DI PUSKESMAS KEDATON - Tasya Ivani Syafira, Tasya Ivani Syafira; Dewiarti, Azelia Nusa (Medula, 2024)
Varicella is a skin infection disease caused by the Varicella zoster virus. WHO estimates that the varicella disease burden is 4.2 million with complications. Applying the principles of family medicine and implementing holistic management based on the patient-centered, family-focused, and community-oriented approach grounded in Evidence Based Medicine. This study is a case report utilizing primary data obtained through anamnesis, physical examination, and home visits to get family, psychosocial, and enviromental data. Secondary data were obtained from the patient’s medical records. A 6-years-old female patient came with small pimples on the face, neck, body, back, arms, thighs from 3 days ago. Patient didn’t care about self-hygiene. Patient rarely take a shower and washing her hands. The patient was diagnosed with varicella. Holistic management was performed with a family physician-designed approach for A 6-years-old female patient, with varicella based on the initial holistic diagnosis. The intervention has improved the patient’s knowledge and changed some behaviours of the patient and her family.